Biases in Recommendations for and Acceptance of Prostate Biopsy Significantly Affect Assessment of Prostate Cancer Risk Factors: Results From Two Large Randomized Clinical Trials - Tangen, Catherine M. (J Clin Oncol, 2016)
PURPOSE: To identify factors related to who undergoes a prostate biopsy in a screened population and to estimate the impact of biopsy verification on risk factor–prostate cancer associations. PATIENTS AND METHODS: Men who were screened regularly from the placebo arms of two large prostate cancer prevention trials (Prostate Cancer Prevention Trial [PCPT] and Selenium and Vitamin E Cancer Prevention Trial [SELECT]) were examined to define incident prostate cancer cohorts. Because PCPT had an end-of-study biopsy, prostate cancer cases were categorized by a preceding prostate-specific antigen/digital rectal examination prompt (yes/no) and noncases by biopsy-proven negative status (yes v no). We estimated the association of risk factors (age, ethnicity, family history, body mass index, medication use) with prostate cancer and quantified differences in risk associations across cohorts. RESULTS: Men 60 to 69 years of age, those with benign prostatic hyperplasia, and those with a family history of prostate cancer were more likely, and those with a higher body mass index (≥ 25), diabetes, or a smoking history were less likely, to undergo biopsy, adjusting for age and longitudinal prostate-specific antigen and digital rectal examination. Medication use, education, and marital status also influenced who underwent biopsy. Some risk factor estimates for prostate cancer varied substantially across cohorts. Black (v other ethnicities) had odds ratios (ORs) that varied from 1.20 for SELECT (community screening standards, epidemiologic-like cohort) to 1.83 for PCPT (end-of-study biopsy supplemented with imputed end points). Statin use in SELECT provided an OR of 0.65 and statin use in in PCPT provided an OR of 0.99, a relative difference of 34%. CONCLUSION: Among screened men enrolled in prostate cancer prevention trials, differences in risk factor estimates for prostate cancer likely underestimate the magnitude of bias found in other cohorts with varying screening and biopsy recommendations and acceptance. Risk factors for prostate cancer derived from epidemiologic studies not only may be erroneous but may lead to misdirected research efforts.